Identification of two novel members of the tentative genus Wukipolyomavirus in wild rodents - Nainys, Juozas; Timinskas, Albertas; Schneider, Julia; Ulrich, Rainer G.; Gedvilaitė, Alma (PLOS ONE, 2015)
Two novel polyomaviruses (PyVs) were identified in kidney and chest-cavity fluid samples of wild bank voles (Myodes glareolus) and common voles (Microtus arvalis) collected in Germany. All cloned and sequenced genomes had the typical PyV genome organization, including putative open reading frames for early regulatory proteins large T antigen and small T antigen on one strand and for structural late proteins (VP1, VP2 and VP3) on the other strand. Virus-like particles (VLPs) were generated by yeast expression of the VP1 protein of both PyVs. VLP-based ELISA and large T-antigen sequence-targeted polymerase chain reaction investigations demonstrated signs of infection of these novel PyVs in about 42% of bank voles and 18% of common voles. In most cases only viral DNA, but not VP1-specific antibodies were detected. In additional animals exclusively VP1-specific antibodies, but no viral DNA was detected, indicative for virus clearance. Phylogenetic and clustering analysis including all known PyV genomes placed novel bank vole and common vole PyVs amongst members of the tentative Wukipolymavirus genus. The other known four rodent PyVs, Murine PyV and Hamster PyV, and Murine pneumotropic virus and Mastomys PyV belong to different phylogenetic clades, tentatively named Orthopolyomavirus I and Orthopolyomavirus II, respectively. In conclusion, the finding of novel vole-borne PyVs may suggest an evolutionary origin of ancient wukipolyomaviruses in rodents and may offer the possibility to develop a vole-based animal model for human wukipolyomaviruses.